Injectable Drug Delivery System Based on In Situ Self‐Assembly of Liquid Star Polyethylene Glycol–Poly(lactic‐co‐glycolic acid). Issue 3 (5th March 2021) - Eylon, Bat-hen; Shagan, Alona; Shabtay-Orbach, Ayelet; Gross, Adi; Mizrahi, Boaz
Abstract : Drug Delivery In article number 2000069, Boaz Mizrahi and co‐workers report a new nano delivery system that is based on injectable liquid copolymer. The copolymer, starPEG‐PLGA (red and blue in the image) is mixed with the drug (green spheres in the image) without any solvents or excipients. After the mixture is injected into the body, the copolymer self‐assembles in situ into well‐defined nanoparticles.